A study of the factors influencing the success of IT-enabled change investments in the UK health sector - Abdul-Karim, Raied Mehdi (Cranfield University, 2010)
The majority of IT projects across various countries and industries fail or do not realise all their intended benefits. Despite previous research into this area and the development of various project success models, IT projects continue to fail at an alarming rate. This research examines the reasons for this phenomenon and extends the existing knowledge by providing insight and learning into how to successfully manage IT enabled change projects within the National Health Service (NHS) in the UK. The research used interpretive, retrospective case studies to examine the outcomes of four IT enabled change projects in the NHS. Forty-three face-to-face, semistructured interviews were conducted to collect a rich source of data for the analysis. A comprehensive body of literature was reviewed and key areas/themes were identified that could be expected to influence project outcomes. These themes were used to develop and structure the interview questions and guide the data analysis. The research was designed to first learn from successful projects and then contrast the findings with those from less successful projects. In the first empirical study, P1, two case studies of successful PACS (Picture Archiving and Communication System) projects in two NHS hospitals were undertaken. The reasons for their success were fully explored and discussed. The second empirical study, P2, consisted of two case studies of less successful projects: the implementations of an electronic Theatre System and an electronic Order Communication System were studied, and the reasons for their lack of success were explored, studied and contrasted with those in P1. Analysis of the evidence from the interviews and review of relevant documents, showed that the main differences between the successful and less successful projects were in the management of the following areas: development of the business case for investment, clinical engagement and involvement, stakeholder management (and, in particular, the clinician/manager relationship), awareness and ownership of benefits, project leadership and the capabilities of the project manager, and the type of the deployed technology. Cont/d.